Healing Effect of Wistar Rat Incision Wounds on Administration of Microemulsion Combination of Green and Red Betel Leaf Extracts - Dewi, Vonny Khresna; Barkinah, Tut; Rizki, Muhammad Ikhwan (Tropical Health and Medical Research, 2024)
One natural ingredient that has the potential to heal wounds is betel leaf. This study aimed to analyze the healing effect of Incision wounds in Wistar rats when administering a microemulsion combination of green and red betel leaf extracts. This research begins with sample collection, drying process, and extraction. The extract was then formulated into emulgel as a microemulsion in three formulations. These three formulas, along with a positive control and a negative control, were tested on each Wistar rat incision wound. The results of the research showed that emulgel formula 3, which was tested on mice, had the best ability to heal wounds for an average of 2.5 days and kept the mice's body temperature normal; 36.6oC. Formula 3 contains 5% South Kalimantan red betel, 5% South Kalimantan green betel, 5% Central Kalimantan red betel, and 5% Central Kalimantan green betel. This proves that the combination of formula 3 can heal wounds and body temperature in experimental mice. Further research is needed to find the best composition that produces faster, more complete wound healing effects and safely impacts experimental animals.